The diagnostic yield of CGH and WES in neurodevelopmental disorders - Alotibi, Raniah S.; Sannan, Naif S.; AlEissa, Mariam; Aldriwesh, Marwh G.; Al Tuwaijri, Abeer; Akiel, Maaged A.; Almutairi, Mashael; Alsamer, Alhanouf; Altharawi, Nouf; Aljawfan, Ghadah; Alotiabi, Badi; AlBlawi, Mohammed A.; et al. (Frontiers in Pediatrics, 2023)
Abstract: Background: Neurodevelopmental disorders are a group of conditions characterized by developmental delays leading to abnormal brain functions. The methods of diagnosis and treatment of these conditions are complicated, and their treatment involves a combination of various forms of therapy. In recent years, the development of high-resolution technologies has played an important role in revealing the micro-deletions, micro-duplications, and single nucleotide variants of the chromosomes and how they are linked to the development of neurodevelopmental disorders. The wide implementation and application of molecular methodologies have started to shed light on the functional importance of using the appropriate methods in detecting these genetic variations that are categorized as either pathogenic or benign. The study aimed to compare the diagnostic yield of CGH and WES in neurodevelopmental disorders among children attending the King Abdullah Specialist Children Hospital, Riyadh, Saudi Arabia. Methods: A retrospective study was conducted between 2015 - 2018 on 105 patients diagnosed with neurodevelopmental disorders through Array-CGH and Whole Exome Sequencing (WES). Results: In a sample of 105 patients, 16% was the hit rate of copy number variations (CNVs). WES was requested for CNVs negative patients (n=79), of which 30% was the hit rate of pathogenic or /likely pathogenic single-nucleotide variants (SNVs). There was a difference in the diagnostic yield between CGH (16%) and WES (30%). Conclusion: WES was a better approach than array-CGH to detect various DNA mutations or variants. Our findings could guide clinicians, researchers and testing laboratories select the most cost-effective and appropriate approach for diagnosing their patients.